Radiology - A Specific Tool in Identification A Review - Vinoth Kumar S; Monisha B. M (Indian Journal of Forensic Medicine & Toxicology, 2021)
Now a days in Forensics, Radiology or Imaging plays a major role in identification of criminal and civilproceedings. Why Radiology here means, it is making bit sensible that to analyze the bony structures likeskeletal remains and other body parts. The main aim of the manuscript is to unite the two disciplines inone part majorly “Radiology and Forensics”. The forensic application of diagnostic medical radiology canbe applied in many fields; the prime target of evaluation is the osseous skeleton, but soft tissues whichmay offer several key findings. Essential, methods consist of radiological methods such as conventionalradiography, computed tomography, and magnetic resonance imaging, but other techniques such as 2D and3D surface scanning along with printing are also employed.